Epistemology of Nusantara Exegesis in the 17th Century: A Study of Tarjumān al-Mustafīd by Abdurrauf al-Singkili - Lail, Moh. Jamalul; Hidayat, M. Riyan; Wijaya, Roma (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
The position of Tarjumān al-Mustafīd by Abdurrauf al-Singkili as a precedent for interpretive literature in Indonesia has ontological problems. Accusations circulated that Tarjumān al-Mustafīd was just a translated copy of al-Baiḍāwi's commentary on Anwār al-Tanzīl wa Asrār al-Ta'wīl. In comparison, other groups consider it a translation of Tafsīr Jalālayn. These two claims seem to cast doubt on Tarjumān Al-Mustafīd as an authentic interpretation work. Every work of interpretation always involves the subjectivity of the interpreter. Through an analysis of the epistemology of interpretation, this research reveals the genealogy, method, and validity of al-Singkili's interpretation in Tarjumān al-Mustafīd. The findings of this research highlight three essential aspects: First, Tarjumān al-Mustafīd is not merely the result of translation (vernacularization) of one particular interpretation as has been alleged so far. Several other tafsir, such as Tafsīr Jalālayn and Tafsīr al-Khāzin, also influenced the presentation pattern of Tarjumān al-Mustafīd. Second, al-Singkili's interpretive method is similar to al-Baiḍāwi but not wholly the same. Al-Singkili also adopted the pattern of writing the Indonesian turath books, which use keywords such as fāidah, tanbīh, the word mufasir, and others. Third, Tarjumān al-Mustafīd qualifies as a valid or authentic interpretation of consistency and correspondence. This research offers a novel contribution by positioning Tarjumān al-Mustafīd as a unique synthesis of classical Islamic exegesis and the scholarly tradition of the Nusantara, demonstrating its originality as an interpretive work that bridges global Islamic scholarship with localized epistemological frameworks.